KAPASITAS PEREMPUAN DI MASA PANDEMI: STUDI CVA PADA PEREMPUAN PERAJIN REYENG - Umami, Rizka Hidayatul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
This paper discusses the capacities of women during the Covid-19 pandemic. In Indonesia, Covid-19 has changed many aspects. Haphazard policy making also adds to the workload of the community, both in the domestic and public sphere. Women as agents who contribute to providing food needs in the realm of the family are almost never included in policy making, especially during the pandemic. This makes the policies issued cannot accommodate the needs of women. Meanwhile, the unfinished pandemic also exacerbates the subordinate conditions experienced by women. This paper uses a gender analysis model of the Capasities and Vulnerabilities Analysis Framework (CVA) to see the extent of the capacities and vulnerabilities of women crafters of reyeng in Dusun Contong, Ngunggahan Village in the midst of the Covid-19 pandemic. The method used in this research is qualitative-descriptive and data collection was taken by observation and in-depth interviews. The results of this study indicate that women crafters of reyeng during the Covid-19 pandemic were vulnerable due to limited access to aspects of health and social assistance. However, these women also have the capacity and capability to adapt to a pandemic. This capability is evidenced by the ability to use the narrow land around the house to grow vegetables and exchange food and bamboo with other reyeng women craftsmen.